Optimizing diagnostic tests for persulphate‐induced respiratory diseases. Issue 1 (21st July 2016) - Foss‐Skiftesvik, M. H.; Winther, L.; Mosbech, H. F.; Skov, P. S.; Opstrup, M. S.; Søsted, H.; Zachariae, C.; Johansen, J. D.; Johnsen, C. R.
Abstract: Background: Persulphates from hair bleaching products are considered the major cause of occupational‐rhinitis and asthma in hairdressers. The specific inhalation challenge (SIC) is considered 'reference standard' for diagnosing persulphate‐induced asthma and rhinitis; however, the currently validated method of performing SIC with persulphate powder is time consuming with a duration of up to 4 days. The value of skin prick tests (SPTs) and histamine release tests (HRTs) with persulphates is unknown. The aim of this study was to establish a novel rapid SIC with persulphate powder to test for both rhinitis and asthma simultaneously in 1 day. In addition, we assessed the suitability of SPTs and HRTs for detecting persulphate‐induced respiratory diseases. Methods: The study population included 19 hairdressers with a history of work‐related rhinitis and/or asthma symptoms, 12 symptomatic controls (10 with concurrent allergic asthma and rhinitis and two with non‐allergic asthma), and 40 healthy controls. A previous severe asthmatic reaction and/or anaphylactic reaction to persulphates was considered an exclusion criterion for hairdressers. The 19 hairdressers and 12 symptomatic controls had SIC performed with 3 × 5 min exposures to potassium persulphate powder in a provocation chamber. All participants, including the 40 healthy controls, were subjected also to SPTs and HRTs with three persulphate salts at concentrations of 2–20 % and 0.03–1 %, respectively. Results: None of the symptomatic controls had a nasal or bronchial response to SIC with potassium persulphate. Six hairdressers presented a nasal and two a bronchial response. No severe reactions occurred. No positive SPTs were recorded, neither among hairdressers, symptomatic controls, nor healthy controls. All three groups showed nonspecific non‐IgE mediated histamine release to persulphates in HRT. Conclusions: The proposed method for performing SIC showed a high specificity for detecting persulphate‐induced asthma and rhinitis. The rapid SIC was able to produce positive nasal and bronchial responses in symptomatic hairdressers without any severe reactions occurring. SPTs and HRTs cannot predict asthma or rhinitis caused by persulphates.